2014
DOI: 10.1111/jvh.12358
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term entecavir or tenofovir disoproxil fumarate therapy in treatment‐naïve chronic hepatitis B patients in the real‐world setting

Abstract: The aim of this study was to determine the long-term efficacy of entecavir (ETV) and tenofovir disoproxil fumarate (TDF) on the natural course of disease in chronic hepatitis B patients (CHB) with/without cirrhosis in clinical practice. A total of 355 treatment-naïve CHB patients were enrolled into the study. The primary outcome measure was viral suppression as defined by serum HBV DNA level <20 IU/mL. A secondary outcome measure was to determine the development of Hepatocellular carcinoma (HCC). Virological a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
48
4
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(65 citation statements)
references
References 19 publications
(30 reference statements)
9
48
4
4
Order By: Relevance
“…As for TDF, it has been indicated that the suppressive effect on HCC seems equivalent to ETV. 21,22 However, further study is necessary because there have only been a small number of reports. Thus, no obvious differences were found between different NA therapies in suppressing HCC among HBV-infected patients with or without cirrhosis.…”
Section: Impact Of Nucleos(t)ide Analogue For Hccmentioning
confidence: 99%
“…As for TDF, it has been indicated that the suppressive effect on HCC seems equivalent to ETV. 21,22 However, further study is necessary because there have only been a small number of reports. Thus, no obvious differences were found between different NA therapies in suppressing HCC among HBV-infected patients with or without cirrhosis.…”
Section: Impact Of Nucleos(t)ide Analogue For Hccmentioning
confidence: 99%
“…There was no significant difference found between the NA in the prevention of HCC. In a study of 355 treatment-naïve patients with CHB, 39.2% of whom had cirrhosis, who received entecavir or tenofovir, Idilman et al [33] found that the cumulative incidence of HCC at 1 year was 3.3% and at 4 years was 7.3%. No significant difference was found between the 2 groups.…”
Section: Impact Of Na Choice On Hcc Incidencementioning
confidence: 99%
“…Yine bu çalışmada hastalık ciddiyetiyle (dekompanse siroz, kompanse siroz ve non-sirotik KHB) HSK riskinin arttığı gösterilmiştir. Bununla birlikte non-sirotik hastalarda da HSK (12). Sunulan olguda siroz yoktur ancak ileri yaş ve myelodisplastik sendromla ilişkilendirilmiş olsa da trombosit düşüklüğü gibi risk faktörleri bulunmaktaydı.…”
Section: İrdelemeunclassified